The Influence of Emotional Intelligence and Workplace Well-Being on Work-Life Balance among Married Female Civil Servants in The Government of Kediri City - Wahyuningtyas; Shine Pintor Siolemba Patiro; Mafizatun Nurhayati (Yayasan Sinergi Kawula Muda, 2026)
This study aims to examine the influence of emotional intelligence and workplace well-being on work-life balance, with employee engagement as a mediating variable. The research focuses on married female civil servants in Kediri. The background of this study is the gender role disparity in Indonesia, where women are often culturally expected to be the primary caregivers at home despite their significant professional roles. This research uses a quantitative approach involving 97 married female civil servants in Kediri. Data were collected through a survey using a questionnaire: emotional intelligence, workplace well-being, employee engagement, and work-life balance. Data analysis was conducted using Partial Least Squares (PLS), a component of Structural Equation Modeling (SEM). PLS was chosen for its capability in testing inter-variable relationships while validating mediation models. Instrument validity and reliability were tested beforehand to ensure data accuracy. The findings indicate that emotional intelligence has a significant positive effect on work-life balance (p=0.000; t=4.585) and employee engagement (p=0.000; t=5.081). Workplace well-being does not have a direct effect on work-life balance (p=0.334; t=0.428), but significantly increases employee engagement (p=0.000; t=4.537). Employee engagement positively mediates the relationship between emotional intelligence and workplace well-being with work-life balance (p=0.002; t=2.860). These findings offer theoretical contributions by strengthening mediation models in the context of gender and public sector, and practical implications for the Government of Kediri.